The financial effect of cross listing on Sub-Saharan African exchanges for Johannesburg Stock Exchange, (JSE), listed companies - Dabengwa, Vusisizwe Noel (My University, 2017)
There are 29 formal stock exchanges on the African continent with 23 based in sub-Saharan Africa. The pace and stage of stock market development has varied among most of the countries as only four stock markets have more than 50 listed stocks; five have at least 20 listed stocks; and the remaining 14 have less than 20 stocks. The Johannesburg Stock Exchange (JSE) stands out in Africa as by far the continent’s largest, most liquid and best regulated market and is home to some of the continent’s largest and most sophisticated companies. Cross listing refers to the listing of ordinary shares of a firm on an exchange other than the stock exchange in its registered jurisdiction. There are 24 JSE listed companies that have cross listed on other Sub-Saharan African stock exchanges. The bulk of these, (14), have cross listed on the Namibia Stock Exchange, 3 cross listed on Botswana Stock Exchange, 1 on the Nairobi Stock Exchange, 1 on the Ghanaian Stock Exchange, 3 on the Malawian Stock Exchange, 1 on the Zambian Stock Exchange and 1 on the Zimbabwean Stock Exchange. The study establishes the possible reasons and benefits of cross listing on other sub-Saharan exchanges for JSE listed companies. The study also provides insight into the possible effects, (financial as well as any others), of cross listing on other sub-Saharan African exchanges that a number of JSE listed entities have experienced. The study uses financial information collected from a public platform, (Sharedata), to compute financial ratio’s to determine the financial implications of the JSE companies cross listing on other sub-Saharan exchanges. The effects of cross listing on the JSE companies are then measured using latent growth curve modelling and a paired t test. The study concludes that there is no evidence to suggest that there are financial benefits for JSE listed companies to cross list on other sub-Saharan exchanges. The study further suggests that JSE listed companies should rather consider cross listing for qualitative reasons rather for any quantitative reasons.
Thesis submitted in fulfillment of the requirements for the degree of Master of Management in Finance & Investment in the Faculty of Commerce, Law and Management Wits Business School at the University of the Witwatersrand 2017
Keywords: Johannesburg Stock Exchange; Securities--Listing; Stock Exchanges--Africa, Sub-Saharan